Impact of the 1115 behavioral health Medicaid waiver on adult Medicaid beneficiaries in New York State. (19th April 2021) - Frimpong, Eric Y.; Ferdousi, Wahida; Rowan, Grace A.; Radigan, Marleen
Abstract: Objective: To evaluate the impact of the Health and Recovery Plan (HARP), a capitated special needs Medicaid managed care product that fully integrates physical and behavioral health delivery systems in New York State. Data Sources: 2013‐2019 claims and encounters data on continuously enrolled individuals from the New York State Medicaid data system. Study Design: We used a difference‐in‐difference approach with inverse probability of exposure weights to compare service use outcomes in individuals enrolled in the HARP versus HARP eligible comparison group in two regions, New York City (NYC) pre‐ (2013‐2015) versus post‐ (2016‐2018) intervention periods, and rest of the state (ROS) pre‐ (2014‐2016) versus post‐ (2017‐2019) intervention periods. Data Collection/Extraction Methods: Not applicable. Principal Findings: HARPs were associated with a relative decrease in all‐cause (RR = 0.78, 95% CI 0.68‐0.90), behavioral health‐related (RR = 0.76, 95% CI 0.60‐0.96), and nonbehavioral‐related (RR = 0.87, 95% CI 0.78‐0.97) stays in the NYC region. In the ROS region, HARPs were associated with a relative decrease in all‐cause (RR = 0.87, 95% CI 0.80‐0.94) and behavioral health‐related (RR = 0.80, 95% CI 0.70‐0.91) stays. Regarding outpatient visits, the HARPs benefit package were associated with a relative increase in behavioral health (RR = 1.21, 95% CI 1.13‐1.28) and nonbehavioral health (RR = 1.08, 95% CI 1.01‐1.15) clinic visits in the NYC region. In the ROS region, the HARPs were associated with relative increases in behavioral health (RR = 1.47, 95% CI 1.32‐1.64) and nonbehavioral health (RR = 1.17, 95% CI 1.11‐1.25) clinic visits. Conclusions: Compared to patients with similar clinical needs, HARPs were associated with a relative increase in services used and led to a better engagement in the HARPs group regardless of the overall decline in services used pre‐ to postperiod.